Meritocracy: China's form of democracy (2021)
This article illustrates China’s meritocracy in light of political, social and cultural differences accounting both for Western and Eastern standards thought to define political systems and governmental regimes. It also shows the factors that make meritocracy a potential “democracy” with Chinese characteristics, explaining the elements of meritocracy throughout history together with the roots of the system in the country. In the process, the article defines both meritocracy and democracy and presents certain factors that may suggest that meritocracy can -for now- be acknowledged as a democracy even when it does not fully agree with Western standards. Throughout academia it is understood that there is no single form of democracy and that each country adapts the system to its own characteristics; making it possible that Chinese meritocracy -with the cultural shifts made- can be better comprehended and accepted as one of these primary forms of democracy.